Novel Temperate Phages of Salmonella enterica subsp. salamae and subsp. diarizonae and Their Activity against Pathogenic S. enterica subsp. enterica Isolates - Mikalová, Lenka; Bosák, Juraj; Hříbková, Hana; Dědičová, Daniela; Benada, Oldřich; Šmarda, Jan; Šmajs, David (PLoS One, 2017)
Forty strains of Salmonella enterica (S. enterica) subspecies salamae (II), arizonae (IIIa), diarizonae (IIIb), and houtenae (IV) were isolated from human or environmental samples and tested for bacteriophage production. Production of bacteriophages was observed in 15 S. enterica strains (37.5%) belonging to either the subspecies salamae (8 strains) or diarizonae (7 strains). Activity of phages was tested against 52 pathogenic S. enterica subsp. enterica isolates and showed that phages produced by subsp. salamae had broader activity against pathogenic salmonellae compared to phages from the subsp. diarizonae. All 15 phages were analyzed using PCR amplification of phage-specific regions and 9 different amplification profiles were identified. Five phages (SEN1, SEN4, SEN5, SEN22, and SEN34) were completely sequenced and classified as temperate phages. Phages SEN4 and SEN5 were genetically identical, thus representing a single phage type (i.e. SEN4/5). SEN1 and SEN4/5 fit into the group of P2-like phages, while the SEN22 phage showed sequence relatedness to P22-like phages. Interestingly, while phage SEN34 was genetically distantly related to Lambda-like phages (Siphoviridae), it had the morphology of the Myoviridae family. Based on sequence analysis and electron microscopy, phages SEN1 and SEN4/5 were members of the Myoviridae family and phage SEN22 belonged to the Podoviridae family.
Keywords: fágy salmonel; Genome, Viral; virová nálož; salmonelóza; Microscopy, Electron; Salmonella Infections; Československo; druhová specificita; genom virový; DNA, Viral; Species Specificity; elektronová mikroskopie; Phylogeny; lyzogenie; mikrobiologie životního prostředí; Salmonella Phages; Viral Load; sekvenční homologie nukleových kyselin; Sequence Homology, Nucleic Acid; Sequence Analysis, DNA; Lysogeny; sekvenční analýza DNA; fylogeneze; Czechoslovakia; Salmonella enterica; DNA virů; Environmental Microbiology